2007
DOI: 10.1002/humu.20564
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genomic copy number changes in patients with idiopathic mental retardation by high-resolution X-array-CGH: important role for increased gene dosage ofXLMRgenes

Abstract: A tiling X-chromosome-specific genomic array with a theoretical resolution of 80 kb was developed to screen patients with idiopathic mental retardation (MR) for submicroscopic copy number differences. Four patients with aberrations previously detected at lower resolution were first analyzed. This facilitated delineation of the location and extent of the aberration at high resolution and subsequently, more precise genotype-phenotype analyses. A cohort of 108 patients was screened, 57 of which were suspected of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
169
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(181 citation statements)
references
References 42 publications
8
169
2
2
Order By: Relevance
“…Although genetic status in other members of the family was not investigated because of a lack of available materials, two of the proband's maternal uncles (II-2, II-3) had MR (Figure 3), suggesting that this deletion was inherited from the proband's mother (II-4) and probably contributes to MR. An oligonucleotide-array analysis revealed that breakpoints of dup(X)(p11.23) and del(X)(p11.22) were mapped within segmental duplications containing SSX genes, GAGE genes and XAGE genes and sequence gap, respectively (Figure 4). Previous reports 13,27 suggested that CNVs at Xp11.22-p11.23 were associated with flanking segmental duplications. In addition, broken forks are the precursor lesions directly processed into segmental duplications in yeast 34 and Fork Stalling and Template Switching (FoSTeS) has been proposed as a replication-based mechanism that produces nonrecurrent rearrangements potentially facilitated by the presence of segmental duplications.…”
Section: Cnvs In Xlmr S Honda Et Almentioning
confidence: 91%
“…Although genetic status in other members of the family was not investigated because of a lack of available materials, two of the proband's maternal uncles (II-2, II-3) had MR (Figure 3), suggesting that this deletion was inherited from the proband's mother (II-4) and probably contributes to MR. An oligonucleotide-array analysis revealed that breakpoints of dup(X)(p11.23) and del(X)(p11.22) were mapped within segmental duplications containing SSX genes, GAGE genes and XAGE genes and sequence gap, respectively (Figure 4). Previous reports 13,27 suggested that CNVs at Xp11.22-p11.23 were associated with flanking segmental duplications. In addition, broken forks are the precursor lesions directly processed into segmental duplications in yeast 34 and Fork Stalling and Template Switching (FoSTeS) has been proposed as a replication-based mechanism that produces nonrecurrent rearrangements potentially facilitated by the presence of segmental duplications.…”
Section: Cnvs In Xlmr S Honda Et Almentioning
confidence: 91%
“…In patient 29, a duplication at Xp11.4 involving the TSPAN7 (OMIM 300096) gene was detected (Figure 3a). TSPAN7 mutations have been associated with X-linked nonsyndromic MR, and a duplication of this gene has been reported in three patients, 38 although the pathogenic function of copy number gains remains controversial. In our case, parents were not available to assess the origin of these CNVs, but in structural abnormalities of the X chromosome, females presenting with a random X-inactivation pattern is associated with a severe phenotype.…”
Section: Detection Of Submicroscopic Imbalances L Bernardini Et Almentioning
confidence: 99%
“…Thus far, only larger-sized (8-21 Mb) Xp22 duplications involving CDKL5 have been described, [31][32][33][34] making phenotypic contribution of CDKL5 duplication challenging to dissect. Here, we correlate genotypes with phenotypes of four males and seven females from seven unrelated families with CDKL5 duplications smaller than 1 Mb in size.…”
Section: Introductionmentioning
confidence: 99%